Bridging Campus to Business World: Roles of Business Literacy and Networking Capability in Enhancing Students’ Entrepreneurial Motivation - Sepvianto, Gersom Arie; Budiyanto, Fajar; Sudarmiatin; Wijijayanti, Trisetia (Cita konsultindo, 2025)
Entrepreneurship is increasingly recognized as a critical component in higher education, especially for management students who are preparing to enter a dynamic business environment. This study investigates the effects of business literacy and networking capability on entrepreneurial motivation among fifth-semester students of the Management Study Program, Faculty of Economics, XYZ University. The research addresses the problem that, despite growing attention to entrepreneurship education, the combined influence of cognitive (business literacy) and social (networking capability) factors on students’ entrepreneurial motivation remains underexplored. Using a quantitative descriptive–correlational method, data were collected from 125 respondents through an online survey and analyzed using multiple linear regression in SPSS version 30. The results show that both business literacy and networking capability have significant positive effects on entrepreneurial motivation, both individually and simultaneously. Among the two predictors, networking capability was found to be the most dominant factor, indicating that strong social relationships and access to professional networks greatly enhance students’ entrepreneurial drive. This study concludes that improving students’ business knowledge and strengthening their networking abilities are essential strategies for fostering entrepreneurial motivation. The findings contribute both theoretically, by integrating cognitive and social perspectives, and practically, by offering insights for designing more effective entrepreneurship education programs. Keywords: Entrepreneurial motivation, business literacy, networking capability.